Exploring technical and vocational education and training and its relationship to employment in Nepal: a mixed methods study - Prakash Kumar Paudel; Mahesh Nath Parajuli; Prakash C Bhattarai (Empirical Research in Vocational Education and Training)
Abstract This study was conducted to explore the relationship between actors of education and employment systems in Nepali Technical and Vocational Education and Training (TVET) system. The study measured the engagement of actors from both systems in the curriculum process: design, application, and feedback phases. Further, it explained why the actors of these systems have weak relationships in Nepal. This study used an explanatory sequential mixed methods approach. First, we collected the information with 124 TVET experts with at least five years of experience to calculate the linkage index score. Second, we interviewed 15 individuals who were the respondents in the first survey. The survey revealed that although the education and employment system has gradually increased collaboration in the last few years, particularly since 2018, education actors still have more power for decision-making across all three curriculum phases. The study revealed that employers’ lack of meaningful participation in the curriculum design phase impedes them from engaging in the curriculum application and excludes them in the feedback phase. This study contributes an essential insight to bridging a gap between actors of the education and employment system.